Pengaruh Terapi Kombinasi Relaksasi Benson Dan Guided Imagery Terhadap Tingkat Kecemasan Pada Ibu Hamil Risiko Tinggi - Agustin, Cindiana Putri Yeni; Martini, Diah Eko; Ekawati, Heny (Universitas Muhammadiyah Lamongan, 2025)
Introduction: High-risk pregnancy is associated with potential dangers and medical complications that may pose serious risks to the mother or fetus, such as hypertension, gestational diabetes, or a history of problematic deliveries. This study aimed to analyze the effect of a combined intervention using Benson Relaxation and Guided Imagery techniques on reducing anxiety levels among high-risk pregnant women. Methods: A pre-experimental design with a one-group pre-test and post-test approach was employed. The study population included pregnant registered at Kedungpring Public Health Center, selected through purposive sampling, yielding a total of 36 participants. The combined therapy was administered twice weekly for one week, with each session lasting 15 minutes. The instruments used in this study were SOP (Benson and guided imagery) and the Depression Anxiety Stress Scales (DASS) anxiety questionnaire. Data were analyzed using the Wilcoxon test. Results: Before the intervention, 83% of participants experienced moderate anxiety. After the intervention, 53% reported mild anxiety. The Wilcoxon test results showed a significant difference in anxiety levels before and after the intervention (p: 0.00). Conclusion: The findings suggest that the combination of Benson Relaxation and Guided Imagery effectively reduces anxiety in high-risk pregnant women and may be considered as supplemental material during antenatal care visits.